Studying the knowledge economy: forming system of indicators - Смаль, Валентина (Human Geography Journal, 2016)
The development of the system of appropriate indices for knowledge economy research is a recognized methodological problem. This article proposes to analyze the level of development of the knowledge economy using two groups of indicators. One group of indicators reveals total spending on Research and Development and their effectiveness. The second set of indicators characterize the economic sectors that consume the new knowledge. Those sectors are the high-tech industries and knowledge intensive service.